Edukasi Gizi Seimbang, Vaksin dan Protokol Kesehatan bagi Remaja SMP PERTIWI 2 Padang Saat Pandemi Covid-19 - Fivi Melva Diana; Najmiatul Fitria; Sri Nani Jelmila; Sari Yulanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Indonesia is experiencing health problems in adolescents, namely the high rate of malnutrition and anaemia in adolescents in Indonesia. Another impact from the Covid-19 pandemic also affects the consumption and immunity of teenagers. Consumption and body immunity are factors that can affect nutritional status. The Covid-19 pandemic changes eating patterns, as well as inhibits and reduces the movement or physical activity of adolescents. Therefore, it is necessary to carry out balanced nutrition education, vaccines, and the application of health protocols during the Covid-19 pandemic. This community service aimed to educate students about balanced nutrition, vaccines, and the application of health protocols to adolescents during the Covid-19 pandemic using leaflets and posters to students at SMP PERTIWI 2 Padang. The method to see respondents' knowledge level was carried out pre-test and post-test on balanced nutrition education, vaccines and the application of health protocols for adolescents at SMP PERTIWI 2 Padang used a questionnaire with 20 questions. This service showed that the respondents' knowledge increased by 11.4%, 80%, in the pre-test to 91.4% in the post-test. This activity can be continued in collaboration with SMP PERTIWI 2 Padang by monitoring nutritional status and product development for teenagers at SMP PERTIWI 2 Padang.